Thermally conductive grease composition

By using liquid dimethylpolysiloxane and ethylene propylene copolymers in thermal conductivity greases and reasonably adjusting the content of thermal conductivity fillers, the existing problems of sagging and high viscosity of thermal conductivity silicon greases are solved, and a thermal conductivity grease composition with low viscosity, high thermal conductivity and heat resistance are achieved.

CN119894983APending Publication Date: 2025-04-25FUJI POLYMER INDUSTRIES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380066884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-06-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing thermally conductive silicon grease is prone to hang when it is vertically clamped by the heat generator and the heat dissipation body, and has a high viscosity, making it difficult to meet the requirements of high thermal conductivity and low viscosity.

Method used

The thermally conductive grease composition containing liquid dimethylpolysiloxane and ethylene propylene copolymer is used to ensure that the composition has good heat resistance and low sagging characteristics at high temperatures by adjusting the viscosity of the matrix resin and the content of the thermally conductive filler.

Benefits of technology

A thermally conductive grease composition with low viscosity but not easy to hang is achieved, with high thermal conductivity, suitable as a thermal interface material, and can maintain good performance at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894983A_ABST
    Figure CN119894983A_ABST
Patent Text Reader

Abstract

The present invention relates to a thermally conductive grease composition containing a matrix resin and a thermally conductive filler. The matrix resin contains a liquid dimethylpolysiloxane (A) having a kinematic viscosity at 40 DEG C of 100-10000 mm2 / s and an ethylene-propylene copolymer (B) having a kinematic viscosity at 40 DEG C of 1-10000 mm2 / s. When the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is taken as 100 parts by mass, the matrix resin contains 50 parts by mass or more and 97 parts by mass or less of the liquid dimethylpolysiloxane (A) and 3 parts by mass or more and 50 parts by mass or less of the ethylene-propylene copolymer (B). This thermally conductive grease composition contains 400-2500 parts by mass of the thermally conductive filler per 100 parts by mass of the total of the liquid dimethyl polysiloxane (A) and the ethylene-propylene copolymer (B).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermally conductive grease composition suitable for being interposed between a heat generating body and a heat radiating body of an electric or electronic component or the like. Background Art

[0002] In recent years, the performance of semiconductors such as CPUs has improved dramatically, but the heat generation has also increased dramatically. Therefore, heat sinks are installed in heat-generating electrical and electronic components, and thermally conductive grease is used to improve the adhesion between heat-generating bodies such as semiconductors and heat sinks. With the miniaturization, high performance, and high integration of electrical and electronic components, thermally conductive grease is required to have high thermal conductivity and the property that the grease is difficult to drip from between the heat-generating body and the heat sink (called "drip resistance").

[0003] Patent document 1 proposes a composition comprising: a thermally conductive filler; a polyorganosiloxane resin containing at least one polysiloxane having one curable functional group in the molecule; and a siloxane compound having an alkoxysilyl group and a linear siloxane structure. Patent document 2 proposes a thermally conductive silicone composition with improved heat dissipation, which contains liquid silicone, a thermally conductive filler and specific hydrophobic spherical silica particles. Patent document 3 discloses a thermally conductive fluorinated adhesive composition containing aluminum oxide of different particle sizes and shapes. The inventor proposed a thermally conductive grease composition containing an ethylene-α-olefin copolymer in Patent documents 4 to 5.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-104714

[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-044213

[0008] Patent Document 3: Japanese Patent Application Publication No. 2017-190389

[0009] Patent Document 4: Japanese Patent No. 7047199

[0010] Patent Document 5: Japanese Patent No. 7095194 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the thermally conductive silicone greases of Patent Documents 1 to 3 have the problem of dripping from between the heating element and the radiator when they are sandwiched vertically between the heating element and the radiator. In addition, the thermally conductive grease compositions of Patent Documents 4 to 5 have the problem of having a higher viscosity than thermally conductive silicone greases.

[0013] The present invention aims to solve the conventional problems and to provide a thermally conductive grease composition which has low viscosity, is not prone to dripping, and has high thermal conductivity.

[0014] Means for solving problems

[0015] The thermally conductive grease composition of the present invention is a thermally conductive grease composition comprising a base resin and a thermally conductive filler, wherein:

[0016] The matrix resin has a kinematic viscosity of 100 to 10000 mm at 40°C. 2 / s of liquid dimethyl polysiloxane (A), and a kinematic viscosity of 1 to 10000 mm at 40°C 2 / s ethylene-propylene copolymer (B),

[0017] When the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is set to 100 parts by mass, the base resin contains 50 parts by mass or more and 97 parts by mass or less of the liquid dimethylpolysiloxane (A) and 3 parts by mass or more and 50 parts by mass or less of the ethylene-propylene copolymer (B),

[0018] The thermally conductive filler is contained in an amount of 400 to 2500 parts by mass based on 100 parts by mass of the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B).

[0019] Effects of the Invention

[0020] In the thermally conductive grease composition containing a base resin and a thermally conductive filler, the base resin contains a kinetic viscosity of 100 to 10000 mm at 40°C. 2 / s of liquid dimethyl polysiloxane (A), and a kinematic viscosity of 1 to 10000 mm at 40°C 2 / s of ethylene-propylene copolymer (B), when the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is set to 100 parts by mass, in the base resin, the liquid dimethylpolysiloxane (A) is 50 parts by mass or more and 97 parts by mass or less, and the ethylene-propylene copolymer (B) is 3 parts by mass or more and 50 parts by mass or less, and the thermally conductive filler is contained in an amount of 400 to 2500 parts by mass relative to 100 parts by mass of the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B). By the above-mentioned configuration, a thermally conductive grease composition with low viscosity, low drooping resistance and high thermal conductivity can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 AB is an explanatory diagram showing a method for measuring the thermal conductivity of a sample in one example of the present invention.

[0022] Figure 2 AD are schematic illustrations for explaining a drop test employed in one embodiment of the present invention. DETAILED DESCRIPTION

[0023] The thermally conductive grease composition of the present invention (hereinafter sometimes referred to as "grease composition") comprises a base resin and a thermally conductive filler, wherein the base resin comprises a thermally conductive filler having a kinematic viscosity of 100 to 10000 mm at 40°C. 2 / s of liquid dimethyl polysiloxane (A), and a kinematic viscosity of 1 to 10000 mm at 40°C 2 / s of ethylene-propylene copolymer (B). The liquid dimethylpolysiloxane (A) has high heat resistance, and the ethylene-propylene copolymer (B) tends to become hard at high temperatures. Therefore, by using the two together in a specific ratio, it is possible to ensure the heat resistance of the grease composition while suppressing sagging by becoming hard at high temperatures. The kinematic viscosity of the liquid dimethylpolysiloxane (A) at 40°C is preferably 100 to 5000 mm 2 / s, more preferably 100 to 3000 mm 2 / s, more preferably 100 to 1000 mm 2 / s, more preferably 100 to 400 mm 2 / s, more preferably 100 to 200 mm 2 The kinematic viscosity of the ethylene-propylene copolymer (B) at 40° C. is preferably 10 to 5000 mm 2 / s, more preferably 100 to 1000 mm 2 / s, more preferably 100 to 800 mm 2 / s, more preferably 100 to 500 mm 2 / s, more preferably 100 to 300 mm 2 / s. Thus, the grease composition of the present invention can have excellent heat resistance and low viscosity but is unlikely to sag when held vertically.

[0024] The ethylene-propylene copolymer (B) is a hydrocarbon-based synthetic oil that does not contain a polar group. Examples of commercially available products include the "LUCANT" series manufactured by Mitsui Chemicals, Inc. The density of the ethylene-propylene copolymer is preferably 0.83 to 0.85 g / cm 3 In this case, there is an advantage that the specific gravity of the grease composition can be reduced. The arrangement of the units derived from ethylene and the units derived from propylene in the ethylene-propylene copolymer (B) may be block or random.

[0025] When the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is set to 100 parts by mass, the content of the thermally conductive filler is 400 to 2500 parts by mass, preferably 600 to 2400 parts by mass, more preferably 800 to 2400 parts by mass, and even more preferably 1000 to 2400 parts by mass. Thus, the grease composition can have a low viscosity but is not easy to sag, and the thermal conductivity can be improved.

[0026] When the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is 100 parts by mass, the content of the liquid dimethylpolysiloxane (A) is 50 parts by mass or more and 97 parts by mass or less, and the content of the ethylene-propylene copolymer (B) is 3 parts by mass or more and 50 parts by mass or less. Preferably, the content of the liquid dimethylpolysiloxane (A) is 55 parts by mass or more and 95 parts by mass or less, and the content of the ethylene-propylene copolymer (B) is 5 parts by mass or more and 45 parts by mass or less. More preferably, the content of the liquid dimethylpolysiloxane (A) is 60 parts by mass or more and 94 parts by mass or less, and the content of the ethylene-propylene copolymer (B) is 6 parts by mass or more and 40 parts by mass or less. Further preferably, the content of the liquid dimethylpolysiloxane (A) is 65 parts by mass or more and 94 parts by mass or less, and the content of the ethylene-propylene copolymer (B) is 6 parts by mass or more and 35 parts by mass or less. As a result, the grease composition can have improved heat resistance, reduced viscosity, and is less likely to droop when held vertically.

[0027] From the viewpoint of achieving low viscosity, sagging suppression, and high thermal conductivity of the grease composition, the thermally conductive filler preferably contains 20 to 2000 parts by mass of alumina having a median particle size of 1 μm or more and 5 μm or less, more preferably 100 to 600 parts by mass, and even more preferably 200 to 500 parts by mass. In addition, the thermally conductive filler preferably contains 20 to 1500 parts by mass of spherical alumina having a median particle size of more than 100 μm, 20 to 500 parts by mass of aluminum nitride having a median particle size of 5 μm or more and 50 μm or less, 20 to 1000 parts by mass of amorphous pulverized alumina having a median particle size of 1 μm or more and 5 μm or less, and 20 to 500 parts by mass of amorphous pulverized alumina having a median particle size of 0.1 μm or more and less than 1 μm. As a result, small particles can exist between large particles, and filling can be performed in a state close to the closest packing, which can improve thermal conductivity, and can further reduce the viscosity of the grease composition and suppress sagging. For the same reason, it is more preferred that the thermally conductive filler contains 500 to 1200 parts by mass of spherical alumina with a median particle size exceeding 100 μm, 50 to 400 parts by mass of aluminum nitride with a median particle size of 5 μm to 50 μm, 100 to 600 parts by mass of amorphous crushed alumina with a median particle size of 1 μm to 5 μm, and 50 to 400 parts by mass of amorphous crushed alumina with a median particle size of 0.1 μm to less than 1 μm. It is further preferred that the thermally conductive filler contains 700 to 1200 parts by mass of spherical alumina with a median particle size exceeding 100 μm, and 100 to 400 parts by mass of aluminum nitride with a median particle size of 5 μm to 50 μm. , amorphous pulverized alumina with a median particle size of 1 μm to 5 μm: 150 to 500 parts by mass, amorphous pulverized alumina with a median particle size of 0.1 μm to less than 1 μm: 100 to 400 parts by mass, and further preferably, the thermally conductive filler contains spherical alumina with a median particle size exceeding 100 μm: 800 to 1100 parts by mass, aluminum nitride with a median particle size of 5 μm to 50 μm: 150 to 400 parts by mass, amorphous pulverized alumina with a median particle size of 1 μm to 5 μm: 200 to 500 parts by mass, and amorphous pulverized alumina with a median particle size of 0.1 μm to less than 1 μm: 100 to 400 parts by mass.

[0028] The spherical alumina having a median particle size exceeding 100 μm is preferably a spherical alumina having a median particle size exceeding 100 μm and 200 μm or less, and more preferably a spherical alumina having a median particle size exceeding 100 μm and 150 μm or less.

[0029] The shape of the aluminum nitride having a median particle size of 5 μm or more and 50 μm or less is preferably amorphous. The aluminum nitride having a median particle size of 5 μm or more and 50 μm or less is preferably aluminum nitride having a median particle size of 5 μm or more and 30 μm or less.

[0030] The median particle size is D50 (median diameter) of the cumulative particle size distribution based on volume measured by a laser diffraction light scattering method. Such a measuring instrument includes, for example, a laser diffraction / scattering particle size distribution measuring device LA-950S2 manufactured by Horiba, Ltd.

[0031] The grease composition of the present invention preferably further contains, as a viscosity modifier, 0.1 to 10 parts by mass of R a Si(OR') 4-a (wherein R is an unsubstituted or substituted organic group having 8 to 12 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) or a partial hydrolyzate thereof. This can reduce the viscosity of the grease composition.

[0032] The thermal conductive filler is preferably R a Si(OR') 4-a (wherein R is an unsubstituted or substituted organic group having 8 to 12 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1) or a partial hydrolyzate thereof is subjected to surface pretreatment. This can reduce the viscosity of the grease composition. In particular, it is preferred to perform surface pretreatment on a small particle size filler having a median particle size of 0.1 μm or more and 5 μm or less.

[0033] As the alkoxysilane compound, for example, octyl trimethoxy silane, octyl triethoxy silane, decyl trimethoxy silane, decyl triethoxy silane, dodecyl trimethoxy silane and dodecyl triethoxy silane can be listed. The above-mentioned alkoxy silane compounds can be mixed and used in one or more kinds. As a surface treatment agent, an alkoxy silane compound and a single-terminal alkylsilanol siloxane can also be used together. The surface treatment mentioned here includes adsorption, etc. in addition to covalent bonds. If surface treatment is performed, the miscibility of the thermally conductive filler and the matrix resin becomes good.

[0034] The alkoxysilane compound is mixed with the thermally conductive filler in advance, and the thermally conductive filler is preferably pretreated with the alkoxysilane compound. It is preferred to add 0.01 to 10 parts by mass of the alkoxysilane compound relative to 100 parts by mass of the thermally conductive filler. By surface treating the thermally conductive filler with the alkoxysilane compound, the thermally conductive filler becomes easier to fill in the matrix resin.

[0035] The thermal conductivity of the thermally conductive grease composition is preferably 1.0 W / m·K to 10.0 W / m·K, more preferably 1.5 W / m·K to 10.0 W / m·K, and even more preferably 2.0 W / m·K to 10.0 W / m·K. Such a thermally conductive grease is suitable as a TIM (Thermal Interface Material).

[0036] The absolute viscosity of the thermally conductive grease composition at 23°C measured by a B-type viscometer at a rotation speed of 5 rpm using a TE spindle is preferably 1000 Pa·s or more and 20000 Pa·s or less, more preferably 1000 Pa·s or more and 18000 Pa·s or less, further preferably 1000 Pa·s or more and 15000 Pa·s or less, and further preferably 1000 Pa·s or more and 10000 Pa·s or less. Thus, a thermally conductive grease composition having excellent workability and good injectability or coating properties between a heat generating body and a heat dissipating body can be obtained.

[0037] 0.4 g of the thermally conductive grease composition is placed between two plates, and the thermally conductive grease composition is sandwiched between the two plates so that the thickness of the layer formed by the thermally conductive grease composition reaches 0.5 mm. The plates are then held in a thermal shock tester with the main surface of the plates perpendicular to the ground. Next, the temperature is raised to 125°C after being held at -40°C for 30 minutes, and then the temperature is lowered to -40°C after being held at 125°C for 30 minutes. This is considered as one cycle. In a thermal shock test performed for 500 cycles, the drop of the thermally conductive grease composition from the start of the test is preferably within 5 mm. This allows the drop resistance to be maintained at a high level.

[0038] The thermally conductive grease composition of the present invention may contain, as required, heat resistance enhancers such as red iron oxide, titanium oxide, cerium oxide, flame retardants, flame retardant aids, etc. In addition, the thermally conductive grease composition of the present invention may contain organic or inorganic particle pigments for the purpose of coloring and toning as required. In addition, the thermally conductive grease composition of the present invention may contain alkoxy-containing silicone for the purpose of surface treatment of thermally conductive fillers as required. The thermally conductive grease composition of the present invention does not particularly require a curing catalyst, and the thermally conductive grease composition of the present invention is preferably a non-curing grease.

[0039] The thermally conductive grease composition of the present invention can be used as a product by filling it in a dispenser, a bottle, a can, a tube, etc.

[0040] In one embodiment, the present invention relates to the use of the thermally conductive grease of the present invention, wherein the thermally conductive grease composition of the present invention is interposed between a heat generating body and a heat radiating body. In one embodiment, the present invention relates to the use of the thermally conductive grease of the present invention, wherein the thermally conductive grease composition of the present invention is interposed between a heat generating body and a heat radiating body, and the thermally conductive grease is vertically sandwiched between the heat generating body and the heat radiating body. Examples of the heat generating body include electronic components such as electrical components or semiconductor elements. Examples of the heat radiating body include radiators, etc.

[0041] Example

[0042] The following examples are used for explanation. The present invention is not limited to the examples. Various parameters were measured by the methods described below.

[0043] <Thermal conductivity>

[0044] The thermal conductivity of the thermally conductive grease composition was measured by Hot Disk (transient plane heat source method) (according to ISO / CD22007-2). The thermal conductivity measuring device 1 is as follows Figure 1 As shown in Figure A, a polyimide film sensor 2 is sandwiched between two samples 3a and 3b, and a constant power is applied to the sensor 2 to make it heat up. The thermal characteristics are analyzed from the temperature rise of the sensor 2. The diameter of the top 4 of the sensor 2 is 7 mm. Figure 1 As shown in FIG. 1B, a double helical structure of electrodes is formed, and a current application electrode 5 and a resistance value electrode (temperature measurement electrode) 6 are arranged at the bottom. The thermal conductivity is calculated by the following formula (Formula 1).

[0045] [Mathematical formula 1]

[0046]

[0047] λ: Thermal conductivity (W / m·K)

[0048] P0: Constant power (W)

[0049] r: Radius of the sensor (m)

[0050] τ:

[0051] α: Thermal diffusivity of the sample (m2 / s)

[0052] t: measurement time (s)

[0053] D(τ): dimensionless function of τ

[0054] ΔT(r): Temperature rise of the sensor (K)

[0055] <Absolute Viscosity of Thermally Conductive Grease Composition>

[0056] The absolute viscosity of the thermally conductive grease composition was measured using a B-type viscometer (HBDV2T manufactured by Brookfield). The absolute viscosity was measured at 23° C. using a TE spindle at a rotation speed of 5 rpm (0.5 rpm in Comparative Examples 3 and 4).

[0057] <Drop Test of Thermally Conductive Grease Composition>

[0058] use Figure 2 AD describes the drop test of the thermally conductive grease composition.

[0059] 0.4 g of the thermally conductive grease composition 14 ( Figure 2 A), a gasket 13 is interposed between the aluminum plate and a glass plate 11 having a length of 40 mm, a width of 100 mm, and a thickness of 5 mm, and the heat conductive grease composition is clamped in such a manner that the thickness thereof reaches 0.5 mm ( Figure 2 B). Figure 2 In B, 15 is a thermally conductive grease composition sandwiched between two plates 11 and 12 in a manner to achieve a thickness of 0.5 mm. Next, the aluminum plate 12 and the glass plate 11 are placed in a thermal cycle tester in a manner such that the main surfaces thereof are perpendicular to the ground. Figure 2 C). 16 is a test piece before the test. After keeping it at -40°C for 30 minutes, the temperature is raised to 125°C, and then kept at 125°C for 30 minutes and then cooled to -40°C. This is considered as one cycle and 500 cycles are performed. After 500 cycles, the test piece is taken out and the thermal conductive grease 15 is observed to see if it falls off. Figure 2 In D, 17 is the test piece after the test, and 18 is the drop distance. In addition, the temperature transition time from -40°C to 125°C and from 125°C to -40°C was set to within 10 minutes, respectively.

[0060] [Judgment criteria]

[0061] A: The drop of grease is within 5mm

[0062] B: More than 5mm

[0063] <Kinematic viscosity>

[0064] In the present application, the kinematic viscosity also includes the catalog values ​​of the examples, and is the kinematic viscosity at 40° C. measured by an Ubbelohde viscometer.

[0065] (Examples 1 to 3, Comparative Examples 1 to 3)

[0066] 1. Raw material ingredients

[0067] (1) Liquid dimethyl polysiloxane

[0068] As the liquid dimethyl polysiloxane (A), a kinetic viscosity of 110 mm at 40° C. was used. 2 / s (product catalog value) dimethyl silicone oil (manufactured by Dow Toray Co., Ltd., trade name "SH200CV110CS", specific gravity 0.97 g / cm 3 ).

[0069] (2) Ethylene propylene copolymer

[0070] As the ethylene-propylene copolymer (B), a copolymer having a kinematic viscosity of 200 mm at 40° C. was used. 2 / s (product catalog value) of ethylene-propylene copolymer (manufactured by Mitsui Chemicals, trade name "LUCANTHC-20", specific gravity 0.83 g / cm 3 ).

[0071] (3) Thermally conductive fillers

[0072] A thermally conductive filler (specific gravity 3.98 g / cm2) was used in which 2.4 g of octyltrimethoxysilane was adsorbed on 100 g of alumina on amorphous pulverized alumina (untreated product) with a median particle size of 0.3 μm (D50 = 0.3 μm). 3 ).

[0073] A thermally conductive filler (specific gravity 3.98 g / cm2) was used in which 1.1 g of decyltrimethoxysilane was adsorbed on 100 g of alumina on amorphous pulverized alumina (untreated product) with a median particle size of 2.3 μm (D50 = 2.3 μm). 3 ).

[0074] Spherical alumina with a median particle size of 105 μm (D50 = 105 μm) (untreated, specific gravity 3.98 g / cm 3 ).

[0075] Amorphous aluminum nitride (without surface treatment and a specific gravity of 3.26 g / cm2) with a median particle size of 15 μm (D50 = 15 μm) was used. 3 ).

[0076] (4) Viscosity regulator

[0077] ·Use decyltrimethoxysilane (specific gravity 0.90g / cm 3 ).

[0078] 2. Hybrid Approach

[0079] The liquid dimethylpolysiloxane, ethylene-propylene copolymer, thermally conductive filler particles, and viscosity modifier were mixed to obtain a thermally conductive grease composition as shown in Table 1 below.

[0080] The thermally conductive grease composition obtained as described above was evaluated. The composition and evaluation results are summarized in Table 1 below.

[0081]

[0082] From the above results, it is understood that Examples 1 to 3 are thermally conductive grease compositions which have low viscosity but are not prone to dripping when held vertically, can be filled with a thermally conductive filler at a high filling rate, and have high thermal conductivity.

[0083] In contrast, the drop test result of Comparative Example 1 was poor because no ethylene-propylene copolymer was added as the base resin. The drop test result of Comparative Example 2 was poor because the content of ethylene-propylene copolymer was low. Comparative Examples 3 and 4 had a high viscosity problem because the content of ethylene-propylene copolymer was too high.

[0084] Industrial Applicability

[0085] The thermally conductive grease composition of the present invention is suitable as a thermal interface material (Thermal Interface Material) interposed between a heat generating body and a heat radiating body such as an electric or electronic component.

[0086] Explanation of symbols

[0087] 1- Thermal conductivity measuring device

[0088] 2 - Sensor

[0089] 3a, 3b - Sample

[0090] 4 - Top of sensor

[0091] 5- Electrode for impressed current

[0092] 6-Resistance value electrode (temperature measurement electrode)

[0093] 11 - Glass Plate

[0094] 12-Aluminum plate

[0095] 13 - Pad

[0096] 14-Thermal conductive grease composition

[0097] 15- Thermally conductive grease composition sandwiched between two plates

[0098] 16 - Test piece before testing

[0099] 17 - Test piece after test

[0100] 18 - Falling distance

Claims

1. A thermally conductive grease composition, comprising a base resin and a thermally conductive filler, wherein: The matrix resin has a kinematic viscosity of 100 to 10000 mm at 40°C. 2 / s of liquid dimethyl polysiloxane (A), and a kinematic viscosity of 1 to 10000 mm at 40°C 2 / s ethylene-propylene copolymer (B), When the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B) is set to 100 parts by mass, the base resin contains 50 parts by mass or more and 97 parts by mass or less of the liquid dimethylpolysiloxane (A) and 3 parts by mass or more and 50 parts by mass or less of the ethylene-propylene copolymer (B), The thermally conductive filler is contained in an amount of 400 to 2500 parts by mass based on 100 parts by mass of the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B).

2. The thermally conductive grease composition according to claim 1, wherein The thermally conductive filler contains 20 to 2000 parts by mass of aluminum oxide having a median particle size of 1 μm or more and 5 μm or less.

3. The thermally conductive grease composition according to claim 1 or 2, wherein The thermally conductive filler contains: 20 to 1500 parts by mass of spherical alumina having a median particle size exceeding 100 μm, 20 to 500 parts by mass of aluminum nitride having a median particle size of 5 μm or more and 50 μm or less, 20 to 1000 parts by mass of amorphous pulverized alumina having a median particle size of 1 μm or more and 5 μm or less, and 20 to 500 parts by mass of amorphous pulverized alumina having a median particle size of 0.1 μm or more and less than 1 μm.

4. The thermally conductive grease composition according to any one of claims 1 to 3, wherein The thermally conductive grease composition further contains 0.1 to 10 parts by mass of R as a viscosity modifier, relative to 100 parts by mass of the total amount of the liquid dimethylpolysiloxane (A) and the ethylene-propylene copolymer (B). a Si(OR') 4-a An alkoxysilane compound or a partial hydrolyzate thereof, wherein R is an unsubstituted or substituted organic group having 8 to 12 carbon atoms, R′ is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1.

5. The thermally conductive grease composition according to any one of claims 1 to 4, wherein The thermally conductive filler is R a Si(OR') 4-a The alkoxysilane compound represented by or its partial hydrolyzate is subjected to surface pretreatment, wherein R is an unsubstituted or substituted organic group having 8 to 12 carbon atoms, R' is an alkyl group having 1 to 4 carbon atoms, and a is 0 or 1.

6. The thermally conductive grease composition according to any one of claims 1 to 5, wherein The thermal conductivity of the thermally conductive grease composition is 1.0 W / m·K or more and 10.0 W / m·K or less.

7. The thermally conductive grease composition according to any one of claims 1 to 6, wherein The absolute viscosity of the thermally conductive grease composition at 23° C. measured by a B-type viscometer is 1000 to 20000 Pa·s.

8. The thermally conductive grease composition according to any one of claims 1 to 7, wherein 0.4 g of the thermally conductive grease composition is placed between two plates. The thermally conductive grease composition is sandwiched between the two plates so that the thickness of the layer formed by the thermally conductive grease composition reaches 0.5 mm. The plates are then held in a thermal shock tester with the main surfaces of the plates perpendicular to the ground. Subsequently, the temperature is raised after being held at -40°C for 30 minutes, and then the temperature is lowered to -40°C after being held at 125°C for 30 minutes. This is regarded as one cycle. In the thermal shock test performed for 500 cycles, the drop of the thermally conductive grease composition from the start of the test is within 5 mm.

Citation Information

Patent Citations

  • Heat-conductive silicone composition and heat-conductive sheet

    JP2016044213A

  • Thermal conductive fluorine adhesive composition and electric and electronic component

    JP2017190389A

  • Thermally conductive polyorganosiloxane composition

    JP2018104714A